Impact of opioids on hospital stay and mortality in patients undergoing abdominal surgeries - Maia, Lucas; Chaves, Isabella; Medeiros, Heitor; Silva, Glauco Francisco; da Silva, Wallace Andrino (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Purpose Postoperative pain management is a critical aspect of surgical care, significantly influencing patient recovery and outcomes. This study aims to evaluate the impact of opioid use on hospital stay and mortality rates among patients undergoing abdominal surgeries in Brazil, where healthcare disparities may affect postoperative outcomes. Methods This observational cross-sectional study was conducted at the University Hospital Onofre Lopes in Natal, Brazil. We included 385 patients aged 18 years or older who underwent abdominal surgery in 2023. Data were collected from medical records, focusing on analgesic therapy, opioid types, dosages, and patient demographics. Statistical analyses were performed using JAMOVI software. Results Opioid consumption was prevalent among the cohort, with 89.6% of patients receiving opioids postoperatively. Tramadol was the most frequently administered opioid, followed by nalbuphine and morphine. Patients treated with morphine had a significantly extended median hospital stay (15.5 days) compared to those receiving tramadol or nalbuphine (2 days). Morphine use was also associated with a higher mortality rate, with these patients being 16 times more likely to die compared to those on weaker opioids. Older age and extended hospital stays were additional risk factors for increased mortality. Conclusion Opioids were used extensively in this cohort as the main analgesic drug for postoperative pain management after abdominal surgeries. Use was associated with prolonged hospital stay and higher probability of death.